2012
DOI: 10.1016/j.jvs.2012.02.034
|View full text |Cite
|
Sign up to set email alerts
|

An integrated biochemical prediction model of all-cause mortality in patients undergoing lower extremity bypass surgery for advanced peripheral artery disease

Abstract: Background Patients with advanced peripheral artery disease (PAD) have a high prevalence of cardiovascular (CV) risk factors and shortened life expectancy. However, CV risk factors poorly predict midterm (<5 years) mortality in this population. This study was designed to test the hypothesis that baseline biochemical parameters would add clinically meaningful predictive information in patients undergoing lower extremity bypass. Methods This was a prospective cohort study of subjects with clinically advanced P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 33 publications
2
20
0
1
Order By: Relevance
“…2). However, this effect was relatively weak (HR 0.97), which, in our opinion, supports the hypothesis that a low cholesterol level in patients with a leg amputation should be recognized, not as an atherosclerosis risk factor, but as a marker of the general severity of a patient's malnutrition status [27]. We also found a strong effect of female gender (HR of about 12), blood creatinine (HR of about 7), and smoking habit (HR of about 4) on the risk of leg amputation (Tab.…”
Section: Discussionsupporting
confidence: 80%
“…2). However, this effect was relatively weak (HR 0.97), which, in our opinion, supports the hypothesis that a low cholesterol level in patients with a leg amputation should be recognized, not as an atherosclerosis risk factor, but as a marker of the general severity of a patient's malnutrition status [27]. We also found a strong effect of female gender (HR of about 12), blood creatinine (HR of about 7), and smoking habit (HR of about 4) on the risk of leg amputation (Tab.…”
Section: Discussionsupporting
confidence: 80%
“…22 These results are relevant because a recent prospective cohort study of 225 patients undergoing lower-extremity bypass had a mean LDL of 63.7 mg/dL (60.9 mg/dL for those on statin therapy and 74.9 for those not on statin therapy at the time of surgery). 23 Thus, a good number of these advanced PAD patients had LDL levels within current guidelines, even without being on a statin at the time of their leg surgery. Yet, in the same cohort, high-sensitivity C-reactive protein levels were notably elevated, with a mean value of 12.0 mg/L (median, 3.0 mg/L).…”
mentioning
confidence: 99%
“…In addition, we used the Kruskal-Wallis test to evaluate differences in CRP levels across the three omega-3 index categories proposed by Harris et al (defined as <4%, 4%–8%, >8%, corresponding to high, intermediate, and low CAD risk, respectively 21 ). Finally, having previously shown that patients with PAD and elevated CRP values have adverse cardiovascular and re-vascularization outcomes 23,40 , we used both unadjusted and fully adjusted logistic models to estimate the association of the omega-3 index with an elevated CRP (>5 mg/dL). Statistical analyses were performed using Stata/SE 12 (StataCorp, College Station, TX).…”
Section: Methodsmentioning
confidence: 99%
“…In patients with stable CAD, the omega-3 index has been inversely associated with inflammation as measured with CRP. 22 It is important to understand whether this relationship exists in patients with PAD as well, as inflammation appears to be more severe in these patients and correlates with poorer outcomes 710,23 . The goal of this study was to determine if the omega-3 index is associated with circulating markers of inflammation and endothelial function in patients with PAD.…”
Section: Introductionmentioning
confidence: 99%